Degraded capability : the media and the Kosovo crisis - Hammond, Phil, 1964-; Herman, Edward S. (Pluto Press, 2000)
'Required reading for anyone wishing to understand the war and the media's role in it.' The New Internationalist.
Keywords: Kosovo War, 1998-1999.; Kosovo War, 1998-1999 -- Press coverage.; Kosovo War, 1998-1999 -- Mass media and the war.; Kosovo War, 1998-1999 -- Propaganda.; Guerre du Kosovo, 1998-1999.; Guerre du Kosovo, 1998-1999 -- Couverture de presse.; Guerre du Kosovo, 1998-1999 -- Propagande.; HISTORY -- General.; SOCIAL SCIENCE -- Media Studies.; Mass media and war; Press coverage; Propaganda; Kosovo (Republic); Serbia; Kosovo-Krieg; Massenmedien; Massamedia.; Oorlogen.; Berichtgeving.; Oorlogspropaganda.; 1998-1999; History